2020
DOI: 10.2196/preprints.24531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

People’s Experiences and Satisfaction With Telehealth During the COVID-19 Pandemic in Australia: Cross-Sectional Survey Study (Preprint)

Abstract: BACKGROUND In response to the COVID-19 pandemic, telehealth has rapidly been adopted to deliver health care services around the world. To date, studies have not compared people’s experiences with telehealth services during the pandemic in Australia to their experiences with traditional in-person visits. OBJECTIVE This study aimed to compare participants’ perceptions of telehealth consults to th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
(17 reference statements)
3
2
0
Order By: Relevance
“…Our main study finding of patients' overall positive experience in using TH is consistent with other similar Australian studies 5,23 as well as international studies. 10,24 An Australian national cross-sectional survey 23 found that more than half (n = 369; 61.9%) of the respondents stated that their TH experience was 'just as good as' or 'better than' their traditional in-person medical care experience. In addition, also aligned with our finding, the study 23 evidenced that people having a history of both depression and anxiety had a poorer experience using TH compared with in-person consultation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our main study finding of patients' overall positive experience in using TH is consistent with other similar Australian studies 5,23 as well as international studies. 10,24 An Australian national cross-sectional survey 23 found that more than half (n = 369; 61.9%) of the respondents stated that their TH experience was 'just as good as' or 'better than' their traditional in-person medical care experience. In addition, also aligned with our finding, the study 23 evidenced that people having a history of both depression and anxiety had a poorer experience using TH compared with in-person consultation.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that certain patients prefer in-person appointments over TH should be considered while planning and delivering care. Our main study finding of patients' overall positive experience in using TH is consistent with other similar Australian studies 5,23 as well as international studies. 10,24 An Australian national cross-sectional survey 23 found that more than half (n = 369; 61.9%) of the respondents stated that their TH experience was 'just as good as' or 'better than' their traditional in-person medical care experience.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations